Protecting aviation safety against cybersecurity threats. Issue 1 (1st February 2022) - Stastny, Peter; Stoica, Adrian-Mihail
Abstract: In Air Traffic Management (ATM), Safety Management Systems (SMS) form the principal vehicle for implementing safety policies, practices and procedures in accordance with internationally agreed Standards. In a constantly changing operating environment, it is essential to maintain SMS effectiveness to maintain and enhance levels of ATM safety. Research at the University Politehnica of Bucharest (UPB) has analysed the major, fast-rising threats to ATM safety emerging in the cybersecurity field, and the related synergies between formal management systems in the fields of security and safety. Its ultimate objective is to assess the feasibility of equipping SMS with protection against security risks, especially cybersecurity. It further explores the potential effects of cybersecurity threats to aviation safety and the available protection mechanisms. In considering the synergies between Security Management Systems and Safety Management Systems in ATM, the possibility of full integration of the two into a single protection system is explored. Whilst, despite similarities, such a combination is not found to be an optimal arrangement, the examination nevertheless enables the derivation of the security measures required in order to enhance the effectiveness of SMS.